IMPLEMENTATION OF THE PROBLEM BASED LEARNING MODEL ON STUDENT LEARNING OUTCOMES IN THE HUMAN CIRCULATION SYSTEM IN CLASS VIII SMP NEGERI 4 STABAT - Dini Anggraini; Azrina Purba; Nurhamimah Rambe (Jurnal Pelita Pendidikan, 2026)
Low student learning outcomes are a common problem at the end of the learning process. The use of inappropriate learning models is one of the causes of low student learning outcomes. This study was conducted with the aim of determining the effect of the problem-based learning model on student learning outcomes in the human circulatory system material for class VIII of SMP Negeri 4 Stabat. This study used a quantitative approach with the Quasi Experiment method. The study population was all grade VIII students. The sampling technique was carried out using a purposive sampling method. The sample group was divided into two classes, namely the control class taught with a conventional learning model and the experimental class taught with a problem-based learning model. Each class will be given a pretest and posttest. The instrument used was a multiple-choice test instrument with 23 questions about the human circulatory system material that had been analyzed for validity, reliability, discriminating power and level of difficulty. Before testing the hypothesis, the data were tested for normality and homogeneity. From the results of the analysis, it was obtained that the sample was normally distributed and categorized as homogeneous. Furthermore, statistical hypothesis testing can be done using the t-test. The results of hypothesis testing with the t-test showed that the calculated t value of 2.88 > the t-table value of 2.01 so that Ho was rejected. This means that there is an influence of the problem-based learning model on student learning outcomes in the human circulatory system material for class VIII of SMP Negeri 4 Stabat.